GENEALOGI PAHAM RADIKAL: ANALISIS HISTORIS TERHADAP PERKEMBANGAN IDEOLOGI RADIKAL ABAD KE-20 - Khoirul, Risalatul Muawana; Almaidatul, Aida Zakhrimatul Umami; Akbar, Rifallah Haikal; Winarto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2025)
This study examines the genealogy of radical ideology in the 20th century, focusing on its development, changes in radical thinking, and the factors that influenced its evolution. In a century full of conflict, revolution, and global change, radical ideologies such as communism and fascism played a central role in shaping social and political order. This study explores the genealogy of radical ideology, including its peak period, when communism and fascism emerged as dominant ideologies. We also reveal changes in radical thinking throughout the 20th century, including the adaptation of these ideologies to historical events and social changes. In addition, this study analyzes the social, political, economic, and technological factors that influenced the development of radical thinking. The results of this study have important implications for understanding the history and socio-political dynamics of the 20th century. In addition, this study is relevant to addressing the challenges of radicalism in the contemporary era by providing insights into the development of radical ideology in the future. This study contributes to the study of ideology, history, and global politics. It can serve as an important reference source for researchers, academics, and policymakers interested in understanding radical ideology and its dynamics of development